Conectando saberes na formação docente campesina em espaços não formais por meio do ensino de ciências - MELO, Veruschka Silva Santos (Universidade Federal do Pará, 2020)
This article aims to understand how non-formal learning spaces can contribute to the linking of scientific knowledge and tradition to the training of teachers who educate in the field in the elementary teaching. It is sought to understand and reflect, through narratives of teachers of Ilha de Fora at Curuçá/PA, how this connection can be conceived. This research is narrative, using the researchtraining as a guide and, therefore, also the Discursive Textual Analysis of Moraes and Galiazzi (2005) as methodological support for analysis. My baseline is the theorists Morin (2001), Santos (2007), Silva (2010) and Almeida (2017) who work with the urgency of knowing this subject in its inherent complexity, turning their eyes both to the scientific field and to that of tradition; besides the discussion of a holistic teacher training from the vision of Nóvoa (1994) and Imbernón (2011). Thus, by targeting the teaching of science through scientific knowledge and tradition, it is possible to break the standardized view of science which provides an important milestone in teacher training courses in the field education from the perspective of non-formal teaching spaces.